Penser et nommer l’inclusion : un horizon pour questionner les pratiques professionnelles dans le champ muséal - Maczek, Ewa; Viau-Courville, Mathieu (Muséologies, 2023)
As a national observatory and think tank on museums and heritage, the Office for Museum Cooperation and Information (OCIM) has for forty years conducted national, territorial and thematic surveys on the development of museums, heritage, and scientific, technical and industrial culture (PCSTI). It is dedicated to understanding how institutional and professional practices evolve and what are the new and emerging trends in the field, and to supporting museum professionals and institutions in developing their projects and missions. This article presents the first results of the surveys “Approches sociales et inclusives des musées et des lieux de culture scientifique” (Social and inclusive approaches to museums and scientific cultural spaces) (2020, n =74) and “Chiffres clés des acteurs du PCSTI” (Key statistics in the field of PCSTI) (2021, data 2020 – n = 196), both intended to show how public engagement is an integral part of professional practices in mediation in the field of PCSTI in France. The two surveys reveal different ways in which inclusion and participation are embodied in the museum context, with their strengths and limitations. The article reflects on the place of ideas such as inclusion in the design of public engagement programs and strategies and how in recent years the vocabulary has evolved from using expressions like “facing the publics” or “for the publics” to the more inclusive “with the publics.” Who do we include under the umbrella expression “with the publics”? What methods can be used –whether new or not– to encourage public participation and inclusion in museums? How do these methods impact on professional mediation practices, exhibition design, management, and more generally museum thinking? Participatory museum, inclusive museum, citizen museum, museum as forum: what are the possible developments? This article provides insight on the relationship between the museum and the public, their roles and levels of engagement; whether the hope of “being inclusive” or “more inclusive” not as a turnkey project but very much as the spark that ignites a gradual shift with lasting impacts.